Is increasing income the only reason for rural labor mobility?—A case study of Heilongjiang, China - Hao, Yanzhi; Chi, Jia; Wang, Gangyi (Frontiers in Sustainable Food Systems, 2023)
It is widely known that rural labor mobility is of utmost importance in the livelihoods of families in rural areas of developing countries. It increases the income and overall labor productivity of rural households, but it also brought many inevitable rural recessions. Existing studies have different views on whether increasing income is the only reason for rural labor mobility. The paper estimates the influencing factors of rural labor mobility and investigates the in-depth research on the causes of rural labor mobility. Based on the micro-survey data of 47 villages in 13 cities in Heilongjiang province, China, from 2014 to 2019. Considering the basic situation of rural families and labor mobility, the actual demand for rural laborers in Heilongjiang province is analyzed. The demand for rural laborers in Heilongjiang province is analyzed in view of the basic situation of rural families and labor mobility. The research results show that increasing income is not the only reason for the flow of rural labor, or that rural labor mobility requires more than just rising incomes.